2008
DOI: 10.1097/mot.0b013e3282faa0dd
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in transfusion practice in liver transplantation

Abstract: Recent studies call for continuing every reasonable effort to minimize the use of blood components and can guide us in new approaches to this vital problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…The variable that has most frequently been related to transfusion is preoperative hemoglobin [2,15,16,18]. In our study, prior lower levels of hemoglobin significantly increased the transfusion requirements of all blood products (RBCs, PCs, FFPs).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The variable that has most frequently been related to transfusion is preoperative hemoglobin [2,15,16,18]. In our study, prior lower levels of hemoglobin significantly increased the transfusion requirements of all blood products (RBCs, PCs, FFPs).…”
Section: Discussionsupporting
confidence: 50%
“…Traditionally, it has been associated with major blood loss and consequently high blood transfusion requirements [1]. During the last decade, some improvements in surgical techniques, anesthetic management, and organ conservation as well as better knowledge of hemostatic disorders during the process have significantly contributed to the reduction of the transfusion needs [2]. In spite of this, a great variability in transfusion rates between centers have been published, ranging between 0 and more than 100 red blood cell (RBC) units transfused during the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Acute volume loading tends to pool in the splanchnic circulation leading to bleeding and hepatic congestion with minimal improvement in cardiac preload or output [63] . Dilution of clotting factors and interruption of clot formation (particularly with colloid administration) can lead to significant clot disturbance [64,65] in this susceptible patient group [44] .…”
Section: Managementmentioning
confidence: 99%
“…Unfortunately, accumulating evidence indicated that transfusion of red blood cell (RBC) increased the adverse event rate and led to poor prognosis in post-transplantation patients (Xia et al, 2006;Scornik et al, 2009;Massicotte et al, 2012;Rana et al, 2013). Although the significant improvement of surgical techniques and anesthetic practice had markedly decreased the transfusion frequency (Ozier et al, 2008) and even some successful cases of transfusionfree organ transplantation were reported (Massicotte , 2012), there was still a considerable variability among medical institutions. The phenomenon could be partially explained by the disparity of surgical practice, anesthetic management, and blood transfusion policy in different centers (Pilar et al, 2015); but the potential pathophysiology remained to be elucidated.…”
Section: Introductionmentioning
confidence: 99%